Detection of T. urartu Introgressions in Wheat and Development of a Panel of Interspecific Introgression Lines - Grewal, Surbhi; Hubbart-Edwards, Stella; Yang, Caiyun; Scholefield, Duncan; Ashling, Stephen; Burridge, Amanda; Wilkinson, Paul Anthony; King, Ian P.; King, Julie (Frontiers in Plant Science, 2018)
Tritcum urartu (2n = 2x = 14, AuAu), the A genome donor of wheat, is an important source for new genetic variation for wheat improvement due to its high photosynthetic rate and disease resistance. By facilitating the generation of genome-wide introgressions leading to a variety of different wheat–T. urartu translocation lines, T. urartu can be practically utilised in wheat improvement. Previous studies that have generated such introgression lines have been unable to successfully use cytological methods to detect the presence of T. urartu in these lines. Many have, thus, used a variety of molecular markers with limited success due to the low-density coverage of these markers and time-consuming nature of the techniques rendering them unsuitable for large-scale breeding programs. In this study, we report the generation of a resource of single nucleotide polymorphic (SNP) markers, present on a high-throughput SNP genotyping array, that can detect the presence of T. urartu in a hexaploid wheat background making it a potentially valuable tool in wheat pre-breeding programs. A whole genome introgression approach has resulted in the transfer of different chromosome segments from T. urartu into wheat which have then been detected and characterised using these SNP markers. The molecular analysis of these wheat-T. urartu recombinant lines has resulted in the generation of a genetic map of T. urartu containing 368 SNP markers, spread across all seven chromosomes of T. urartu. Comparative analysis of the genetic map of T. urartu and the physical map of the hexaploid wheat genome showed that synteny between the two species is highly conserved at the macro-level and confirmed the presence of the 4/5 translocation in T. urartu also present in the A genome of wheat. A panel of 17 wheat-T. urartu recombinant lines, which consisted of introgressed segments that covered the whole genome of T. urartu, were also selected for self-fertilisation to provide a germplasm resource for future trait analysis. This valuable resource of high-density molecular markers specifically designed for detecting wild relative chromosomes and a panel of stable interspecific introgression lines will greatly enhance the efficiency of wheat improvement through wild relative introgressions.